Antimicrobial Evaluation of Latex and TLC Fractions from the Leaves of Aloe adigratana Reynolds. (27th March 2020) - Asmerom, Demoze; Hailu, Gebremedhin Solomon; Yimer, Ebrahim M.; Bitew, Helen; Kahsay, Getu
Abstract : Background . The highest prevalence and emergence of microbial infections coupled with the threat of antimicrobial resistance constitute a global concern, which entails searching for novel antimicrobial agents. Medicinal plants are among the major sources of medicines for novel drug discovery. Aloe adigratana is one of the endemic Aloe species in Ethiopia where the leaf latex of the plant is traditionally used for the treatment of various pathogenic conditions such as wound, dandruff, malaria, and diabetes. In spite of such claims, there was no scientific study done so far. The aim of the current study was, therefore, to evaluate the antimicrobial effect of leaf latex of A. adigratana and its thin layer chromatography (TLC) fractions. Methods . Thin layer chromatography (TLC) separation was employed for isolation of bioactive compounds. Agar well diffusion and microdilution assay method were used to evaluate the antimicrobial actions of the leaf latex and TLC fractions against six bacterial strains and four Candida species of reference and clinical isolate microbial strains. Results . Three major fractions, AA01, AA02, and AA03, were identified by TLC. Among the tested microbial strains, the reference strain of Staphylococcus aureus ATCC 29213 (MIC = 0.06 mg/mL) and clinical Candida krusei 242/18 (MIC = 0.14 mg/mL) exhibited higher susceptibility towards AA02, while reference strains of Klebsiella pneumoniae ATCC 700603 (MIC = 0.19 mg/mL) revealed the highest susceptibility towards AA01. The leaf latex displayed the highest activity against Staphylococcus aureus ATCC 29213 and clinical Candida krusei 242/18 with a MIC value of 0.19 mg/mL. Conclusion . The leaf latex and TLC fractions were found to be active against the tested bacterial and Candida species. Therefore, this finding supports the traditional claim of Aloe adigratana and the need for characterization of the TLC fractions to provide as lead compounds for further comprehensive antibacterial and antifungal activities.